Wan Lan, The Blue and the Black (trad. David L. Steelman), Taiwan, Chinese Materials Center Publications, 1987, 536 pp. - Connelly, Marisela (Estudios de Asia y África, 1989)
Peng Ko, Black Tears, Stories of War-Torn China (trad. Nancy Ing), Taiwan, Chinese Materials Center Publications, 1986, 213 pp. (Asian Library Series, num. 33.)